ZAKRES PODMIOTOWY UCHWAŁ W SPRAWACH CEN I OPŁAT ZA USŁUGI KOMUNALNE ORAZ ZA KORZYSTANIE Z OBIEKTÓW I URZĄDZEŃ UŻYTECZNOŚCI PUBLICZNEJ - Zaborniak, Paweł (Wydział Prawa i Administracji UAM, 2003)
There is a limited scope of entities covered by the resolutions taken under art. 4 section 2 point 1 of the Polish Act on Municipal Management (ugk). Within this scope there are local governments implementing the budgetary economy and carrying out municipal functions. The above mentioned scope also includes joint-stock companies and limited liability companies that are provincial, county or district legal entities as understood in the local government legislation. As lex internae, the provisions of the aforesaid resolutions can only be binding for entities subjected to local governments and remain optional for all other entrepreneurs and citizens as an offer of municipal services. This offer need not be final and as in any other case it can be modified through negotiations before the contract terminates. Since a resolution made under art. 4 section 2 point 1 of the Polish Act on Municipal Management is not a local law act, entities not subject to provincial, county or district organs must not be obliged to accept any prices or fees and can offer any rates in any course that best suit their needs. It should be emphasised that management internal resolutions do not provide sufficient grounds to impose obligations and therefore no one can be forced to follow them except for organisationally subjected entities. It remains a separate question whether the citizens of a local government unit will be able to use services offered by a private competitor, as otherwise a municipal enterprise could dominate a certain type of services. Lack of such a possibility would mean a direct force to use the services of municipal enterprises, thus indicating the weakness of the local market rather than the omnipotence of the local government.
SCOPE OF ENTITIES COVERED BY ACTS ON PRICES AND FEES FOR MUNICIPAL SERVICES AND USE OF PUBLIC UTILITIES